(untitled) (Fisioterapia e Pesquisa, 2020)
The handgrip strength in women with rheumatoid arthritis may be compromised, considering the presence of deformities and functional restrictions imposed by the disease. There is insufficient information on the difference in handgrip strength and functionality among middle-aged and older women with rheumatoid arthritis. The aim was to compare handgrip strength, functional capacity and fatigue among middle-aged and older women with rheumatoid arthritis and to verify the association of these variables in the different age groups. Women with rheumatoid arthritis, older than 45 years, with independent gait, were divided into groups of middle-aged (45-59 years) and older women (60 years and over). Handgrip strength (Jamar® dynamometer), functional capacity (gait speed) and fatigue (Functional Assessment of Chronic Illness Therapy) were measured. Statistical comparisons were made between groups by the independent Student’s t-test and the association between variables in each group by Pearson’s correlation test. The significance level considered was 5%. There was a significant difference in handgrip strength between groups (p=0.01). In the adult group, there was an association between functional capacity and fatigue (r=0.53, p=0.01) and in the elderly women group, there was an association between handgrip strength and gait speed (r=0.51, p=0.02). The results showed that the older women were in better muscle conditions. Parameters indicated as markers of functional and muscle performance in elderly women were shown to be associated, confirming the use of these markers in this specific condition.